Isolation and characterization of lambda specialized transducing bacteriophages carrying Klebsiella pneumoniae nif genes. - MacNeil, D (1980)
Seve lambda dnif specialized transducing bacteriophages were isolated from Escherichia coli strains containing plasmids carrying the his-nif region of Klebsiella pneumoniae. These phages collectively carry deoxyribonucleic acid for all of the genes in the nif regulon and adjacent deoxyribonucleic acid of K. pneumoniae. The phages were isolated by using Mu insertions in the nif region to direct the integration of lambda pMu phages in nif via formation of lambda pMu-Mu dilysogens which, upon induction, yielded lambda dnif phages. This procedure should be generally applicable for isolating lambda specialized transducing phages carrying genes from E. coli or other bacteria.